Analysis of Students' Errors in Solving Surface Area Problems of Spherical Solids Based on Newman’s Error Analysis Theory - Azkiana, Alifah; Nopriana, Tri; Aminah, Neneng (International Journal of Geometry Research and Inventions in Education, 2025)
The topic of curved surface solids, especially the surface area of a sphere, is essential for solving contextual mathematical problems. However, limited research has examined students’ difficulties in this area, particularly using Newman's Error Analysis (NEA). This qualitative study aims to identify and analyze students’ errors in solving surface area problems of spheres through NEA. Five 9th-grade students from a public junior high school in Cirebon were selected via purposive sampling. Data were collected through tests and interviews, then analyzed descriptively based on Newman's stages. Triangulation and member checking ensured data validity. Results show that the most frequent errors occurred in the final answer stage, where students failed to reach the correct solution. Errors in process skills were also significant—students could choose the correct formula but struggled with calculations. These findings suggest a need for improved instructional strategies that emphasize conceptual understanding and process fluency. Interactive teaching, visual aids, and targeted practice can help students better comprehend spherical geometry. The study underscores the importance of addressing specific learning obstacles to enhance students’ mathematical problem-solving skills.